2=10+z-3

Rewrite the equation as 10+z-3=2.

10+z-3=2

Move the negative in front of the fraction.

10-z3=2

Subtract 10 from both sides of the equation.

-z3=2-10

Subtract 10 from 2.

-z3=-8

-z3=-8

Multiply both sides of the equation by -3.

-3⋅(-z3)=-3⋅-8

Simplify -3⋅(-z3).

Cancel the common factor of 3.

Move the leading negative in -z3 into the numerator.

-3⋅-z3=-3⋅-8

Factor 3 out of -3.

3(-1)⋅-z3=-3⋅-8

Cancel the common factor.

3⋅-1⋅-z3=-3⋅-8

Rewrite the expression.

-1⋅(-z)=-3⋅-8

-1⋅(-z)=-3⋅-8

Multiply.

Multiply -1 by -1.

1⋅z=-3⋅-8

Multiply z by 1.

z=-3⋅-8

z=-3⋅-8

z=-3⋅-8

Multiply -3 by -8.

z=24

z=24

Solve for z 2=10+z/-3